CALCULATION OF PASSENGER ЕLEVATOR LOADING BASED ON THE MAXIMUM PASSENGER FLOW RATE - Boiko, Andrii; Malishevskyi, Serhiy; Ivanov, Vasyl (SWorld-Ger Conference proceedings, 2024)
The paper considers a simplified methodology for calculating the load and performance of passenger elevators. It is emphasized that the actual average daily load of the elevator differs from the calculated one. The necessity of development of new methods